The way storytellers communicate to influence the audience's reactions in the Kumpul Dongeng Surabaya Community - Nabila Mustikaning Tyas (DIGICOM : Jurnal Komunikasi dan Media, 2023)
Realizing that not everyone can tell stories well and engagingly, a researcher is interested in investigating the communication patterns of storytellers in creating audience responses in the "Kumpul Dongeng Surabaya" community. The goal is to understand the methods or communication patterns storytellers use to deliver their stories.Using a qualitative descriptive method, the researcher employs the S-O-R (Stimulus-Organism-Response) theory, which aims to determine: 1. Stimulus, 2. Organism, and 3. Response through observations, data collection, and interviews with four informants (storytellers and audience members) from the "Kumpul Dongeng Surabaya" community in order to obtain accurate data. To ensure that their stories captivate the audience and prevent them from losing interest, storytellers must skillfully design themes that cater to the audience's needs. Additionally, storytellers utilize vocal intonation and nonverbal cues, as well as visual aids such as puppets, wayang (traditional Javanese shadow puppets), illustrations, clowns, and sound effects. Furthermore, in the storytelling group, the message (stimulus) conveyed to evoke the storyteller's response should also be delivered using a structured scheme.